The contribution of female military peacekeepers towards operational effectiveness in United Nations Organization Stabilization mission in the Democratic Republic of the Congo (MONUSCO) - Komsana, Caroline Nomthandazo (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMil)--Stellenbosch University, 2025.